Boosting Adoption of Coffee Management Practices in Uganda (beyond). The climate smart investment pathway approach and the farmer segmentation tool - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The two approaches of Step-wise investment pathway and farmer segmentation that is being promoted by the CCAFS partners through the learning alliances have gained interest from multiple partners including Olam international. Olam works with a total of 25,000 coffee farmers in Uganda. Olam has sponsored field trials and they plan to roll out the practice to their coffee farmers. Uganda Coffee Development Authority has also expressed interest to have step-wise investment incorporated in the national coffee extension systems and manuals.